Imagem de poeta: Vinicius de Moraes e a organização da Antologia poética - Rafael Martins da Costa (2019)
This dissertation analyzes how Vinicius de Moraes was able to fashion a particular public image of himself as a poet through the process of organizing his own Antologia poética (Selected Poems) – in which he would also suggest a persuasive way of understanding the development of his poetry. The starting point is the assumption that a book of poems is not a mere collection of texts but rather an organic construct much determined by the author’s poetics, contemporary debates, personal commitments and some forsaking as well. Paratextual elements and archive materials such as rough drafts and letters are thus examined in order to discuss the reasons that may lie behind the decisions taken by Vinicius while selecting from his previous books for a first anthology, in the late 1940s. In the preface he wrote especially for this selection, the poet outlines a broad narrative about his own poetical progress – which has proved very effective, as it was later reinforced by many critics and writers, in different contexts, and has since become the most acknowledged interpretation of both his career and poetry. In this text the author advances his idea of an oeuvre divided in two contrasting phases, changing from mystical and “bourgeois” origins into a more socially-concerned verse, so that the Selected Poems as a whole would testify to the poet’s “struggle against himself towards his own liberation” (MORAES, 1954, p.6. Despite this narrative of change, it is possible to establish strong elements of continuity in Vinicius’ work, especially the pervasiveness of myths about the poet and his inspiration. In view of these elements, it should be interesting to reevaluate the terms that are often used for describing Vinicius’ poetics, which are so indebted to the dichotomy that was introduced by the author himself. The opposing phases he suggests, in fact, participate in a series of images articulated in different spots of his poetry that may be identified in the very body of poems collected in the Antologia. This approach may thus emphasize the importance of the book’s materiality, exploring poetical meanings that come forth from just the particular arrangement of the poems included – in such a way to underscore the characteristics that define the complexity and the beauty of Vinicius’ poetry.